2021
DOI: 10.1038/s41598-021-91807-x
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid-enriched plant-based RUTF treatment was not inferior to peanut-milk RUTF treatment in restoring plasma amino acid levels among patients with oedematous or non-oedematous malnutrition

Abstract: Ready-to-use therapeutic food (RUTF) with adequate quality protein is used to treat children with oedematous and non-oedematous severe acute malnutrition (SAM). The plasma amino acid (AA) profile reflects the protein nutritional status; hence, its assessment during SAM treatment is useful in evaluating AA delivery from RUTFs. The objective was to evaluate the plasma AAs during the treatment of oedematous and non-oedematous SAM in community-based management of acute malnutrition (CMAM) using amino acid-enriched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Until recently the guidelines for the formulation of RUTF stated that at least 50% of the protein should be derived from dairy sources; however in 2022 the Codex Alimentarius Commission adopted new guidelines on RUTF with protein quality now of greater importance than protein type, stipulating that cereals, legumes, seeds, or any other locally available ingredients can be used together with/instead of dairy protein, as long as a protein digestibility corrected amino acid score (PDCAAS) of ≥0.9 is achieved . Efforts are ongoing to reformulate RUTF with alternative protein sources, with several published studies and clinical trials investigating the use of legumes and cereals such as soy, oat, rice, sesame, chickpea, sorghum, and maize. …”
Section: Upcycled Bsg and World Hungermentioning
confidence: 99%
“…Until recently the guidelines for the formulation of RUTF stated that at least 50% of the protein should be derived from dairy sources; however in 2022 the Codex Alimentarius Commission adopted new guidelines on RUTF with protein quality now of greater importance than protein type, stipulating that cereals, legumes, seeds, or any other locally available ingredients can be used together with/instead of dairy protein, as long as a protein digestibility corrected amino acid score (PDCAAS) of ≥0.9 is achieved . Efforts are ongoing to reformulate RUTF with alternative protein sources, with several published studies and clinical trials investigating the use of legumes and cereals such as soy, oat, rice, sesame, chickpea, sorghum, and maize. …”
Section: Upcycled Bsg and World Hungermentioning
confidence: 99%
“…In addition, two countries in Europe (France and Italy) were also involved in developing the RUTF products during its initial development [ 2 ], and with more advanced technology [ 30 , 39 ]. In Africa, the ingredients are mostly combined with sorghum, maize, and chickpea and were recently improved with the crystalline amino acid-enriched plant [ 45 , 46 ]. While in Asia, the combination of rice, cereals, legumes, and animal sources [ 38 , 37 ] were usually used, as well as omega 3 and omega six sources [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…The efficacy of amino acid-enriched plant-based (soy, maize, and sorghum) RUTF treatment is not inferior to peanut-milk RUTF treatment in reestablishing plasma amino acid concentrations in SAM children with oedematous or non-oedematous malnutrition [ 45 ]. An efficacy study of the plant-based RUTFs (with or without milk) in Malawi showed both were as efficacious as PM-RUTF in the treatment of patients with SAM in terms of recovery rates and were more efficacious in alleviating anemia and restoring body iron stores in children aged 6–59 months suffering from oedematous and non-oedematous malnutrition [ 46 , 80 , 81 ].…”
Section: Resultsmentioning
confidence: 99%
“…Given this information, the source of Met (in the form of plant or animal protein) also needs to be carefully considered while re-assessing the Met life cycle as suggested by Neubauer and Landecker (2021). Sato et al (2021) have demonstrated the potential of amino acidenriched plant-based therapeutic food for restoring amino acids levels in plasma of malnourished people. With the increasing concern for environmental and health-related issues, it is necessary to make a thorough scientific assessment of the current knowledge to guide administrative policies around human food components.…”
Section: Role Of Dietary Methionine In Animal Systemsmentioning
confidence: 99%
“…Given this information, the source of Met (in the form of plant or animal protein) also needs to be carefully considered while re-assessing the Met life cycle as suggested by Neubauer and Landecker (2021) . Sato et al. (2021) have demonstrated the potential of amino acid-enriched plant-based therapeutic food for restoring amino acids levels in plasma of malnourished people.…”
Section: Introductionmentioning
confidence: 99%